2019
DOI: 10.1093/deafed/enz025
|View full text |Cite
|
Sign up to set email alerts
|

Home Literacy Environment and Emergent Skills in Preschool Children With Hearing Loss

Abstract: Home literacy practices reported by parents of preschool children with hearing loss were compared to those reported by parents of their peers with typical hearing. Parents completed a questionnaire from Boudreau, D. (2005. Use of a parent questionnaire in emergent and early literacy assessment of preschool children. Language, Speech, and Hearing Services in Schools, 36, 33–47. doi:10.1044/0161-1461(2005/004)) assessing home literacy practices across areas such as parent facilitation of literacy and time spent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…Other studies have included opportunities for caregivers to practice the learned skills with their child while they are given guided feedback from researchers or provided instructions regarding skills to work on (Bergeron, 2013;Van der Lam et al, 1995). Parent facilitation of literacy alone has not been shown to correlate with emergent literacy skills of children who are DHH, but rather children's engagement in books has been shown to play a significant role in acquisition of literacy (Reynolds & Werfel, 2019), thus further supporting the need for interactive trainings. An application component for caregivers to practice trained skills with their children has shown to impact both parent and child behaviors (Roberts, 2019;Sacks et al, 2014) and may assist in making trainings even more interactive, less overwhelming to caregivers, and, ultimately, more parent friendly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have included opportunities for caregivers to practice the learned skills with their child while they are given guided feedback from researchers or provided instructions regarding skills to work on (Bergeron, 2013;Van der Lam et al, 1995). Parent facilitation of literacy alone has not been shown to correlate with emergent literacy skills of children who are DHH, but rather children's engagement in books has been shown to play a significant role in acquisition of literacy (Reynolds & Werfel, 2019), thus further supporting the need for interactive trainings. An application component for caregivers to practice trained skills with their children has shown to impact both parent and child behaviors (Roberts, 2019;Sacks et al, 2014) and may assist in making trainings even more interactive, less overwhelming to caregivers, and, ultimately, more parent friendly.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Reynolds and Werfel (2019) found that hearing parents of children who are DHH reported reading to their child for the same number of hours and starting around the same age as hearing parents of hearing children. This recent body of literature also supports a distinct relation between children's engagement and interaction with books during shared reading times and their levels of emergent literacy skills, such as vocabulary, phonological awareness, and print knowledge (Reynolds & Werfel, 2019). Parent training programs have also been proven to support language abilities in children who are DHH (Lund, 2018;Roberts, 2019).…”
mentioning
confidence: 99%
“…Researchers have also begun to explore the impact of HLE on literacy development of children with hearing loss (Twitchell et al, 2015;Andrews et al, 2017;Reynolds and Werfel, 2020). Socioeconomic status (SES) is closely related to HLE.…”
Section: Home Literacy Environmentmentioning
confidence: 99%
“…Early studies on SES's influence on literacy ability of children with hearing loss have shown that SES is an important predictor of their reading ability development (Twitchell et al, 2015). A study on HLE and literacy development of 22 children with hearing loss and 27 children with typical levels of hearing has shown that family reading investment on children with hearing loss, especially in books, is significantly related to children's literacy ability (Reynolds and Werfel, 2020). Further, an intervention activity that provided children with hearing loss with a 1-year reading intervention, including story reading and shared reading activities 20 times a week, has shown that the increase of reading participation has a significant impact on the improvement of children's literacy skills (Andrews et al, 2017).…”
Section: Home Literacy Environmentmentioning
confidence: 99%
See 1 more Smart Citation